2017
DOI: 10.1177/0018720816687205
|View full text |Cite
|
Sign up to set email alerts
|

A Little Anthropomorphism Goes a Long Way

Abstract: Objective We investigated the effects of exogenous oxytocin on trust, compliance, and team decision making with agents varying in anthropomorphism (computer, avatar, human) and reliability (100%, 50%). Background Recent work has explored psychological similarities in how we trust human-like automation compared to how we trust other humans. Exogenous administration of oxytocin, a neuropeptide associated with trust among humans, offers a unique opportunity to probe the anthropomorphism continuum of automation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(17 citation statements)
references
References 128 publications
(208 reference statements)
2
15
0
Order By: Relevance
“…Thus, regarding the transferability of interpersonal trust dynamics to HRI, anthropomorphism of robots might be a relevant determinant. Accordingly, study results support a positive relationship between anthropomorphic design cues, e.g., humanlike appearance or voice of robots (Hancock et al, 2011;van Pinxteren et al, 2019) as well as agents, in general, and trust in such (e.g., Pak et al, 2012;de Visser et al, 2016de Visser et al, , 2017. Furthermore, Kulms and Kopp (2019) explored the role of anthropomorphism and advice quality, a sort of robot competence, in trust within a cooperative human-agent setting.…”
Section: Transferability Of Determinants Of Trust Development In Interpersonal Interaction To Hrisupporting
confidence: 54%
“…Thus, regarding the transferability of interpersonal trust dynamics to HRI, anthropomorphism of robots might be a relevant determinant. Accordingly, study results support a positive relationship between anthropomorphic design cues, e.g., humanlike appearance or voice of robots (Hancock et al, 2011;van Pinxteren et al, 2019) as well as agents, in general, and trust in such (e.g., Pak et al, 2012;de Visser et al, 2016de Visser et al, , 2017. Furthermore, Kulms and Kopp (2019) explored the role of anthropomorphism and advice quality, a sort of robot competence, in trust within a cooperative human-agent setting.…”
Section: Transferability Of Determinants Of Trust Development In Interpersonal Interaction To Hrisupporting
confidence: 54%
“…Further routes for future examination include biological mechanisms for treating ingroup robots nearly as well as ingroup humans. For example, prior work indicates that oxytocin accounts for greater trust and compliance with automated agents ( De Visser et al, 2017 ). Further, oxytocin is shown to motivate people for greater favoritism ( De Dreu et al, 2011 ) and protection ( De Dreu et al, 2012 ) of the ingroup.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one study showed that OXT enhanced levels of trust following social exclusion in the Cyberball game, but only in individuals who reported a negative emotional response to being excluded (Cardoso et al, 2013), and another showed that interpersonal trust was only increased in Democrats with low initial personal trust (Merolla et al, 2013). Finally, one study has reported that intranasal OXT enhanced trust/compliance with reliable, but not unreliable, human-like automatons (De Visser et al, 2017).…”
Section: Oxytocin and Interpersonal Trust In Other Contextsmentioning
confidence: 99%